LONG-TERM RESULTS OF VIDEO-ASSISTED THORACOSCOPIC AND THORACOTOMY OPERATIONS DURING PULMONARY ECHINOCOCCECTOMY - Usmanov X. S; Allanazarov J.A; Sahiboev D.P (Western European Studies, 2024)
Improve the results of surgical treatment of children with echinococcal lung disease through the use of new technologies.
Keywords: Echinococcus lung; videothoracoscopy; trocars